Spontaneous air leak in a Pediatric Emergency Department: An 11-year experience - Luís,Telma (2022)
Abstract Introduction: Due to lack of data, the management of air leaks in children and adolescents is based on protocols for adults. In this study, the authors review and report their institutional experience in the area. Methods: Retrospective and descriptive study of spontaneous air leak cases diagnosed in a Portuguese Pediatric Emergency Department (PED) between January 2007 and December 2018. Results: Twenty-one episodes of spontaneous air leak were diagnosed in 16 patients (87.5% male), with a mean (± standard deviation) age of 14.3 (± 5.1) years. Eighteen cases of spontaneous pneumothorax were reported, fifteen of which primary (eleven first-time episodes and four recurrences) and three secondary (two first-time episodes and one recurrence) to asthma. Three cases of pneumomediastinum with subcutaneous emphysema were identified, two of which related to infection. Smoking habits and/or recent physical activity were major triggers. Pleuritic chest pain was the most frequent symptom on admission. Conservative treatment was the only approach used in six cases. Most cases required thoracic drainage, five of which required surgical intervention. Discussion: This study shows similar demographic features, triggers, and clinical presentation to those reported in the literature for these cases. The management of the condition was based on recommendations established for adults. Conclusion: Although spontaneous air leak is an uncommon condition, it is a reality in PED. Prospective studies in pediatric age are required to develop adequate recommendations for children and adolescents.